Redness as Perceived through the Eyes of the Romans - Czapińska-Bambara, Marta; Danek, Zbigniew (Collectanea Philologica, 2021)
The article is an attempt to revise the long-established belief in the alabaster-white exterior shape of Roman antiquity, which in fact turns out to be full of colours that bring life to its image. The authors implement this intention by indicating how intensely the colour red was present in the reality described by classical Latin authors – contrary to the accusation that one of the participants of the discussion on this subject in Aulus Gellius’ Attic Nights (Gell. Noc. Att. 2.26) makes of the alleged poverty regarding various shades of red in Latin terminology. The material presented contradicts the opinion expressed in Gellius’ text, and at the same time makes us realise how colourful and lively the world that emerges from the literary works of the classical Roman period was. In comparison with it, the reality witnessed by the literature of the Christian era – this parallel is what the authors of the article focus on, concluding their deliberations – in which red becomes almost exclusively a sign of shame, turns out to be ascetically sterile and depressingly colourless.